PEMAHAMAN PRINSIP GERAKAN MUSLIM MODERN AL-RUJŪ‘ ILA AL-QUR’ĀN WA AL-SUNNAH - Rohmatul Maulidiana Aulia (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
The main problem discussed in this paper is Islamic Renewal by the Modern Muslim movement. This movement is a response to the reality of Muslims who contradict the understanding of ijtihad Modern Muslims. Under the pretext of enforcing the authority of the Qur'an and sunna consequently so that Muslims can practice and re-live the pure teachings of Islam and revive the spirit of ijtihad and leave the habit of taklid. This paper discusses the understanding of al-Rujū 'ila al-Qur'an wa al-Sunnah, especially by modernists. This paper will describe analytically and critically explore the modernist view of the principle of al-Rujū 'ila al-Qur'an wa al-Sunnah.